The Cypriot indigenous grapevine germplasm is a multi-clonal varietal mixture - Grigoriou, Apostolis; Tsaniklidis, Georgios; Hagidimitriou, Marianna; Nikoloudakis, Nikolaos (My University, 2020)
Cypriot vineyards are considered as one among the earliest niches of viticulture and a pivotal hub for the domestication and dissemination of grapevine. The millennial presence of Vitis spp. in this Eastern Mediterranean island has given rise to a plethora of biotypes that have not been adequately characterized, despite their unique attributes and stress tolerance. This ancient germplasm also has an additional value since it survived the phylloxera outbreak; hence, it possesses a large amount of genetic diversity that has been unnoticed. In order to provide useful insights to the lineage of Cypriot vineyards, a two-year-spanning collection of centennial grapevine cultivars mostly regarded to belong to four indigenous variety clusters (“Mavro”, “Xynisteri”, “Maratheftiko”, and “Veriko”) was initiated. There were 164 accessions across the broader Commandaria wine zone sampled and characterized using a universal microsatellite primer set. Genetic analysis indicated that considered indigenous Cypriot germplasm has a polyclonal structure with a high level of heterozygosity. Moreover, several lineages or unexplored varieties may exist, since a larger than considered number of discrete genotypes was discovered. Furthermore, it was established that grapevine lineages in Cyprus were shaped across eras via clonal, as well as, sexual propagation. The special attributes of the Cypriot landscape are discussed.
Keywords: Cyprus; Domestication; Microsatellites; Vitis vinifera subsp. sativa; Vitis vinifera subsp. Sylvestris